A method to analyze the living spaces of wheelchair users using IFC - TÜRKYILMAZ, EMRAH (Elsevier Science Bv, Sara Burgerhartstraat 25, Po Box 211, 1000 AE Amsterdam, Netherlands, 2016)
Full physical adequacy for individuals is a temporary condition. Everyone has some limitations on the part of his life. Disabled people have some special needs. However, design for disabled are still made generic. The conventional methods are used to control the design and results are not satisfactory. BIM (Building Information Modeling) is such a good option to control the design. In this study, a method that analyzes the living spaces by using BIM model was developed. While using proposed model, it is possible to define all incompatibilities properly and use them as design feedback to create effective living spaces for wheelchair users. (C) 2016 The Authors. Published by Elsevier Ltd.
Keywords: IFC; BIM; universal design; code checking; Life